National Policy Innovation Reflections: Advancing Sustainable Policies to Reducing Waste - Saputra, Anggara Setya; Kurniasih, Denok; Setyoko, Paulus Israwan (Journal of Governance, 2024)
Increasing national waste volumes are causing significant environmental and public health issues. There is a need for policy innovation to tackle waste management issues. This research aims to understand new methods that led to formulating national-level policies to reduce waste. A literature review was used as the research method to understand how policy innovation can be used further to reduce the volume of waste. Searches were made in Google Scholar and Scopus with the keywords "policy innovation" and "waste reduction." The new methods derived from the research and the formulation of the framework can be brought into use by the authorities. The results of the research provided a framework for innovative waste-reduction policies. The framework was developed using Technical Regulations, Public Private Partnerships, Circular Economy and Incentive-Disincentive Policies. Technical Regulations provide the legislation and technical foundation for proper waste management. Public-private partnerships ensure that private sector expertise and resources are used in such a way that sustainability goals can be met. Circular Economy details ways how consumption of resources can be altered to make it more sustainable and reduce wastage. Incentive-Disincentive Policies are used to enforce a particular behavior or acceptance of a policy. These frameworks can be helpful for the government and stakeholders to understand how innovative steps can be implemented to solve waste problems and how sustainable development can be used to catch up with the national waste crisis.